Detection of BCR-ABL Positive Cells in an Asymptomatic Patient: A Case Report and Literature Review. (14th February 2010) - Bayraktar, Soley; Goodman, Mark
Abstract : We report a case of an asymptomatic 39-year-old male who was incidentally found to have a white blood cell count of 15 000/mm 3 associated with a positive BCR-ABL/ t (9;22)(q34;q11) chromosomal translocation detected in 51/300 of cells by FISH and RT-PCR from peripheral blood. Within the next 3 months, leukocytosis spontaneously subsided; however, BCR-ABL by RT-PCR and FISH was persistent both in peripheral blood and bone marrow. The patient was not started on any therapy and is being followed regularly with laboratory checkup and physical examination for monitoring signs and symptoms of chronic myeloid leukemia (CML) and biological behavior of his BCR-ABL transcripts. At 1 year of surveillance, he is disease free; however he has persistent detection of BCR-ABL fusion gene. Our case is challenging because actual risk of developing CML in BCR-ABL positive healthy, asymptomatic patients is not known.